Researching Gender-Based Violence : Embodied and Intersectional Approaches - Wies, Jennifer R.; Whittaker, Catherine; Tynes, Brendane; Small, Jamie L.; Schwarz, Corinne; Powell, Amber Joy; Petillo, April D.J; Petillo, April D. J.; Mulla, Sameena; Moore, Dawn; Mokhtar, Hasnaa; Hofeller, Stephanie; et al. (Book collections on Project MUSE., 2022)
An interdisciplinary collection of critical, feminist reflections on interpersonal gender violenceDespite the growing interest in the subject of gender violence, surprisingly little has been written in recent years about the methodology behind this emerging field of research. This interdisciplinary collection seeks to fill this gap by empowering scholars to conduct gender violence research in ways that deconstruct rather than reinforce existing power structures and hierarchies. The book argues for new approaches to research and activism on gender-based violence grounded in the intersectional realities of individuals and communities. Each chapter discusses the role of reflective methodologies to recognize institutional and intersectional inequalities, challenging the reader to contemplate ethical considerations of an embodied feminist methodology when researching gender-based violence. By centering these issues for applied scholars, practitioners, and academic activists, the book offers insights about where sociocultural notions of criminality and innocence might align across geographies of gender-based violence.The volume encourages further thinking about embodied methodological creativity in and for the future of interpersonal gender-based violence research. A powerful tool for conducting productive scholarship, Researching Gender-Based Violence provides recommendations for interrogating, practicing, and collaborating across fields, disciplines, and lived realities.